2010
DOI: 10.1007/s00484-010-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of grapevine yield in the Port Wine region under present and future climate conditions

Abstract: The impact of projected climate change on wine production was analysed for the Demarcated Region of Douro, Portugal. A statistical grapevine yield model (GYM) was developed using climate parameters as predictors. Statistically significant correlations were identified between annual yield and monthly mean temperatures and monthly precipitation totals during the growing cycle. These atmospheric factors control grapevine yield in the region, with the GYM explaining 50.4% of the total variance in the yield time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
70
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 33 publications
7
70
1
Order By: Relevance
“…van Leeuwen et al 2004, Santos et al 2011, can directly and indirectly affect vine physiology, growth and stages of development (Magalhães 2008). In fact, regardless of all technical and scientific achievements (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…van Leeuwen et al 2004, Santos et al 2011, can directly and indirectly affect vine physiology, growth and stages of development (Magalhães 2008). In fact, regardless of all technical and scientific achievements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, local and regional atmospheric forcing have an important influence on grapevine phenology (Jones & Davis 2000a), yield (Bindi et al 1996, Santos et al 2011) and wine quality (Rodó & Comín 2000, Esteves & Orgaz 2001, Grifoni et al 2006, Orlandini et al 2009) in different European regions. As an illustration, high correlations between grapevine yield and mean large-scale atmospheric patterns in March, May and June (from budburst to berry set) were found for the Douro Region, Portugal (Santos et al 2011). Similar results were obtained for Bordeaux, France, where enhanced frequency of anticyclonic systems (warm and dry conditions) during flowering and berry set promotes higher wine production.…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing the influence of climate variability and change in viticulture are particularly pertinent, as climate is the leading factor for grapevine yield and quality (van Leeuwen et al 2004, Santos et al 2010) and for grapevine global geographical distribution (Jones 2006). In effect, grapevines have very specific climatic requirements: they are a heat-demanding crop, needing proper high radiation intensities and temperatures, not only during their vegetative growth and development, but also for berry ripening, since they are also highly sensitive to late frost occurrences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The timing and duration of the grapevine phenological stages are deeply tied to the prevailing atmospheric conditions (Jones and Davis, 2000), which also contribute to variability in grapevine yield (Santos et al, 2011), wine production and quality (Fraga et al, 2014). Sabon et al (2002) observed that wines produced in the areas furthest to the south of the Valley of Rhone, where maturation occurs early, had high aromatic composition, low total acidity and high potential alcohol in their must.…”
Section: Introductionmentioning
confidence: 99%